Neuroplastin 65 deficiency reduces amyloid plaque formation and cognitive deficits in an Alzheimer’s disease mouse model - Wu, Dan-Dan; Cheng, Jie; Zheng, Ya-Ni; Liu, Yu-Tong; Hou, Shuang-Xin; Liu, Li-Fen; Huang, Liang; Yuan, Qiong-Lan (Frontiers in Cellular Neuroscience, 2023)
Alzheimer’s disease (AD) is characterized by increasing cognitive dysfunction, progressive cerebral amyloid beta (Aβ) deposition, and neurofibrillary tangle aggregation. However, molecular mechanisms of AD pathologies have not been completely understood. As synaptic glycoprotein neuroplastin 65 (NP65) is related with synaptic plasticity and complex molecular events underlying learning and memory, it is thus hypothesized that NP65 would be involved in cognitive dysfunction and Aβ plaque formation of AD. For this purpose, we examined the impact of NP65 in the transgenic amyloid precursor protein (APP)/presenilin 1 (PS1) mouse model of AD. We found that loss of NP65 alleviated the cognitive deficits of APP/PS1 mice. In addition, Aβ plaque burden and Aβ levels were significantly reduced in NP65-deficient APP/PS1 mice compared with control animals. NP65-loss in APP/PS1 mice resulted in a decrease in glial activation and the levels of pro-inflammatory cytokines (IL-1β, TNF-α, and IL-4) as well as matrix YM-1 and Arg-1, but had no effect on microglial phenotype. Moreover, NP65 deficiency significantly reversed the increased 5-hydroxytryptamin (serotonin) receptor 3A (Htr3A) expressions in hippocampus of APP/PS1 mice. Together, these findings identify a previously unrecognized role of NP65 in cognitive deficits and Aβ formation of APP/PS1 mice and suggest that NP65 may serve as a potential therapeutic target for AD.